Formation of N-nitrosamines from chlorination and chloramination of molecular weight fractions of natural organic matter - Kristiana, Ina; Tan, J.; Joll, Cynthia; Heitz, Anna; Von Gunten, U.; Charrois, Jeffrey (IWA Publishing, 2013)
N-Nitrosamines are a class of disinfection by-products (DBPs) that have been reported to be more toxic than the most commonly detected and regulated DBPs. Only a few studies investigating the formation of N-nitrosamines from disinfection of natural waters have been reported, and little is known about the role of natural organic matter (NOM) and the effects of its nature and reactivity on the formation of N-nitrosamines. This study investigated the influence of the molecular weight (MW) characteristics of NOM on the formation of eight species of N-nitrosamines from chlorination and chloramination, and is the first to report on the formation of eight N-nitrosamines from chlorination and chloramination of MW fractions of NOM. Isolated NOM from three different source waters in Western Australia was fractionated into several apparent MW (AMW) fractions using preparative-scale high performance size exclusion chromatography. These AMW fractions of NOM were then treated with chlorine or chloramine, and analysed for eight species of N-nitrosamines. Among these N-nitrosamines, N-nitrosodimethylamine (NDMA) was the most frequently detected. All AMW fractions of NOM produced N-nitrosamines upon chlorination and chloramination. Regardless of AMW characteristics, chloramination demonstrated a higher potential to form N-nitrosamines than chlorination, and a higher frequency of detection of the N-nitrosamines species was also observed in chloramination.The results showed that inorganic nitrogen may play an important role in the formation of N-nitrosamines, while organic nitrogen is not necessarily a good indicator for their formation. Since chlorination has less potential to form N-nitrosamines, chloramination in pre-chlorination mode was recommended to minimise the formation of N-nitrosamines. There was no clear trend in the formation of N-nitrosamines from chlorination of AMW fractions of NOM. However, during chloramination, NOM fractions with AMW <2.5 kDa were found to produce higher concentrations of NDMA and total N-nitrosamines. The precursor materials of N-nitrosamines appeared to be more abundant in the low to medium MW fractions of NOM, which correspond to the fractions that are most difficult to remove using conventional drinking water treatment processes. Alternative or advanced treatment processes that target the removal of low to medium MW NOM including activated carbon adsorption, biofiltration, reverse osmosis, and nanofiltration, can be employed to minimise the formation of N-nitrosamines.